2016
DOI: 10.18632/oncotarget.8969
|View full text |Cite
|
Sign up to set email alerts
|

S100A4 drives non-small cell lung cancer invasion, associates with poor prognosis, and is effectively targeted by the FDA-approved anti-helminthic agent niclosamide

Abstract: S100A4 (metastasin-1), a metastasis-associated protein and marker of the epithelial to mesenchymal transition, contributes to several hallmarks of cancer and has been implicated in the progression of several types of cancer. However, the impacts of S100A4 signaling in lung cancer progression and its potential use as a target for therapy in lung cancer have not been properly explored. Using established lung cancer cell lines, we demonstrate that S100A4 knockdown reduces cell proliferation, invasion and three-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 39 publications
1
53
0
Order By: Relevance
“…Among them, nine proteins, including ANXA4, EPS8L2, HCCR1, HLA‐DPB1, HLA‐DRA1, HPRT1, LMP2, S100A4 and TOX, have been reported to be involved in cancer progression as shown in Figure A. Growing evidence indicates that elevated S100A4 protein levels are associated with the progression and angiogenesis of several malignant tumors, including breast cancer, non‐small cell lung cancer, prostate cancer, and colon cancer . Therefore, we hypothesized that OSX might exert its effects on cell migration and angiogenesis by regulating S100A4 expression in breast cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, nine proteins, including ANXA4, EPS8L2, HCCR1, HLA‐DPB1, HLA‐DRA1, HPRT1, LMP2, S100A4 and TOX, have been reported to be involved in cancer progression as shown in Figure A. Growing evidence indicates that elevated S100A4 protein levels are associated with the progression and angiogenesis of several malignant tumors, including breast cancer, non‐small cell lung cancer, prostate cancer, and colon cancer . Therefore, we hypothesized that OSX might exert its effects on cell migration and angiogenesis by regulating S100A4 expression in breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Vessel density and S100A4 expression correlated positively in primary tumors from patients with breast cancer . S100A4 is a well established marker and mediator of metastatic disease . However, the upstream molecular signaling pathway involved in S100A4‐mediated metastasis is less well defined.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we found that the knockdown of DPP9 also reduced the expression of MUC1 and S100A4 (mesenchymal markers). The expression of these proteins were previously shown to correlate with poor survival in NSCLC patients,42, 43 while their knockdown suppresses tumor growth and metastasis in NSCLC cells 43, 44. Our investigation of apoptosis‐related protein expression detected a significantly increased expression of p53, BAX, and APAF1, which all play a crucial role in cell apoptosis 45, 46…”
Section: Discussionmentioning
confidence: 98%
“…The S100A4+ cells partially or completely engulfed the cartilage areas of the bronchial graft 4 weeks after transplantation. The S100A4 protein has previously been established as a regulator of metalloproteinases and cytoskeleton activities in solid malignancies, including lung cancer . Recently, Stewart et al .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Stewart et al . reported in vitro experiments showing that S100A4 blockage is associated with reduced proliferation and decreased invasion in a large panel of lung cancer cell lines. The authors used niclosamide, a well‐known antihelminthic agent, to inhibit S100A4 signaling with promising results.…”
Section: Discussionmentioning
confidence: 99%